Protein Kinase C-θ (PKC-θ) in Natural Killer Cell Function and Anti-Tumor Immunity - Anel, Alberto; Aguiló, Juan I.; Catalán, Elena; Garaude, Johan; Rathore, Moeez G.; Pardo, Julián; Villalba, Martín (Frontiers in Immunology, 2012)
The protein kinase C-theta (PKCtheta), which is essential for T cell function and survival, is also required for efficient anti-tumor immune surveillance. Natural killer (NK) cells, which express PKCtheta, play a prominent role in this process, mainly by elimination of tumor cells with reduced or absent major histocompatibility complex class-I (MHC-I) expression. This justifies the increased interest of the use of activated NK cells in anti-tumor immunotherapy in the clinic. The in vivo development of MHC-I-deficient tumors is much favored in PKCtheta-/- mice compared with wild-type mice. Recent data offer some clues on the mechanism that could explain the important role of PKCtheta in NK cell-mediated anti-tumor immune surveillance: some studies show that PKCtheta is implicated in signal transduction and anti-tumoral activity of NK cells elicited by interleukin (IL)-12 or IL-15, while others show that it is implicated in NK cell functional activation mediated by certain killer activating receptors (KAR). Alternatively, the possibility that PKCtheta is involved in NK cell degranulation is discussed, since recent data indicate that it is implicated in microtubule-organizing center (MTOC) polarization to the immune synapse in CD4+ T cells. The implication of PKC isoforms in degranulation has been more extensively studied in CTL, and these studies will be also summarized.